Short-term outcomes of physical activity counseling in in-patients with Major Depressive Disorder: Results from the PACINPAT randomized controlled trial - Cody, Robyn; Beck, Johannes; Brand, Serge; Donath, Lars; Faude, Oliver; Hatzinger, Martin; Imboden, Christian; Kreppke, Jan-Niklas; Lang, Undine E.; Ludyga, Sebastian; Mans, Sarah; Mikoteit, Thorsten; et al. (Frontiers in Psychiatry, 2023)
Introduction: A physical activity counseling intervention based on a motivation-volition model was developed and delivered to in-patients with Major Depressive Disorders with the aim of increasing lifestyle physical activity. The aim of this study is to evaluate the short-term outcomes of this intervention. Methods: A multi-center randomized controlled trial was conducted in four Swiss psychiatric clinics. Adults who were initially insufficiently physically active and were diagnosed with Major Depressive Disorder according to ICD-10 were recruited. The sample consisted of 113 participants in the intervention group (Mage = 42 years, 56% women) and 107 in the control group (Mage = 40 years, 49% women). Motivation and volition determinants of physical activity were assessed with questionnaires. Implicit attitudes were assessed with an Implicit Association Test. Physical activity was self-reported and measured with hip-worn accelerometers over 7 consecutive days starting on the day following the data collection. Results: According to accelerometer measures, step count decreased on average 1’323 steps less per day (95% CI = -2’215 to -431, p < 0.01) over time in the intervention group compared to the control group. A trend was recognized indicating that moderate-to-vigorous physical activity decreased on average 8.37 minutes less per day (95% CI = -16.98 to 0.23, p < 0.06) over time in the intervention group compared to the control group. The initial phase of the intervention does not seem to have affected motivational and volitional determinants of and implicit attitudes towards physical activity. Conclusion: Physical activity counseling may be considered an important factor in the transition from in-patient treatment. Methods to optimize the intervention during this period could be further explored to fulfill the potential of this opportunity. Trial registration: ISRCTN, ISRCTN10469580, registered on 3rd September 2018, https://www.isrctn.com/ISRCTN10469580